Morphological characters and phylogenetic analysis reveal a new species within the Ganoderma lucidum complex from South Africa - Xing, Jia-Hui; Song, Jie; Decock, Cony; Cui, Bao-Kai (Phytotaxa, 2016)
Ganoderma is a well-known genus of polypores because of its important medicinal properties. The genus is typified by G. lucidum, which represents a species complex. Ganoderma aridicola sp. nov. is proposed as a new member of the G. lucidum complex from South Africa based on the combination of morphological and molecular evidences. The new species is characterized by its fuscous to black pileal surface with distinct concentric zones and small pores; in addition, it was found in an environment with contrasted dry and humid seasons. Phylogenetically, sequences data from nuclear internal transcribed spacer regions (ITS) and the translation elongation factor 1-α gene (EF1-α) confirmed that G. aridicola is a new species within the G. lucidum complex.